Evaluation of Precast Beam To Column Connection Using Finite Element Method - Nurul Afiq Abdul Halim (School of Environmental Engineering, Universiti Malaysia Perlis, 2016)
The objectives of this study are to develop finite element model of precast concrete beam-to-column connection. To investigate the behavior of precast concrete beam-to-column connections by using numerical modeling using LUSAS software. To analyze the performance of finite element model subjected to vertical load in term of stress, strain and deformation.